Fatigue Analysis of Relocatable Offshore Platform in Shallow Water Marginal Fields - Abdul Rahim, Ameir Yusuf (Universiti Teknologi PETRONAS, 2020)
Marine and Offshore structures are huge and complex structural systems, commonly fabricated by using steel tubular members interconnected through welded joints. Relocatable offshore platform has the capability to quickly produce small dispersed oil fields due to its mobility which allows it to float over and relocate to other fields after each production completion. These offshore structures will be reused multiple times throughout their operation life and are predominantly subjected to continuous oscillatory environmental loads and one of the primary modes of failure is fatigue. Thus, fatigue analysis is very important in order to determine the fatigue life of an offshore structure based on the fatigue stress cycle. Therefore, the main objective of this project is to conduct deterministic fatigue analysis for a new concept of relocatable offshore platform that can be used in shallow water. Deterministic approach was selected due to its practicality and ease of use. This analysis is conducted in the engineering software SESAM. GeniE is a tool for the modelling of high-level geometry beams and stiffened plates.